Oceanographic Characteristics in the Three International Indonesian Archipelago Sea Lanes (IASLs) Region: Implications for Underwater Acoustics System - Putra, I Wayan Sumardana Eka; Atmadipoera, Agus Saleh; Manik, Henry Munandar; Harsono, Gentio; Purwandana , Adi (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract Highlight Research The IASL-1 entry portal in the southern and northern regions shows the emergent SOFAR channels. The shadow zone and the existence of a SOFAR deep sound channel in the IASL-2 and IASL-3 routes can be triggered by the emergent “saddle” SVP pattern.  The variability seasonally and interannually due to variations in seawater properties stratification plays an important role in SOFAR channel appearances in IASLs. The diverse oceanographic characteristics of IASLs necessitate the implementation of sustainable marine geospatial data. Abstract Indonesian Maritime Continent (IMC) is responsible for the three international sea lanes, known as Indonesian Archipelago Sea Lanes (IASLs), which allowed ships to navigate across territorial waters between Pacific and Indian Oceans and vice versa. Gaining knowledge about the distinct oceanographic characteristics of the three IASLs can offer valuable insight into maritime safety and sustainable marine resource management. Therefore, this research aims to review oceanographic characteristics in IASLs regions from available previous research to provide a comprehensive insight into the processes and dynamical oceanography in IASLs region as well as determine the implications for underwater acoustic patterns. The results showed that IASL-1 route is characterized by a shallow shelf passage with homogeneous sound velocity profile (SVP), which has a deep and narrow entry portal in the southern and northern Sound Fixing and Ranging Channel (SOFAR) channels. Seasonal reversal monsoonal wind-driven current dominates the circulation. IASL-2 and IASL-3 routes transported a deep and narrow passage with complexity of seaair interactions that vary on seasonal and interannual time scales. These IASLs were established with the saddle SVP, which trigger the shadow zone and the existence of SOFAR deep sound channel with seasonal and interannual variations in seawater properties stratification. The diverse oceanographic characteristics discussed significantly influence the underwater object detection equipment, the planning time, and the strategies for underwater defense systems. Due to the implications, it is necessary to use marine geospatial database, which may be adopted to facilitate policy-making, providing approximations for marine activities and management along IASLs.